Amendment of the cytokine profile in macrophages subsequent to their interaction with smooth muscle cells: Differential modulation by fractalkine and resistin. (July 2016) - Tucureanu, Monica Madalina; Butoi, Elena; Gan, Ana-Maria; Stan, Daniela; Constantinescu, Cristina Ana; Calin, Manuela; Simionescu, Maya; Manduteanu, Ileana
Highlights: Macrophage-SMC cross-talk impacts on cytokine expression in macrophages. Fractalkine is an important mediator in macrophage-SMC interaction. Different roles of fractalkine and resistin on macrophage cytokine profile. The secretome of macrophage-SMC co-culture induces monocyte chemotaxis. Abstract: In atherosclerotic plaques, macrophages (MAC) and smooth muscle cells (SMC) frequently reside in close proximity and resistin (Rs) and fractalkine (Fk) are present at increased levels, resistin being associated with CD68 macrophages and fractalkine predominantly associated with intimal SMC; however, their role in this location is not clear, yet. The objective of this study was to determine whether the cross-talk between MAC-SMC induces changes in MAC cytokine phenotype and if Fk and Rs have a role in the process. To this purpose, macrophages (THP-1 monocytes differentiated with phorbol myristate acetate) were interacted with SMC cultured on the membrane inserts in the presence or absence of Rs or Fk. After 24 h, MAC were removed from the co-culture and the gene and protein expression of 57 cytokines was assessed by QPCR and Proteome Profiler™ Array. Fk secreted in the culture medium following MAC-SMC interaction was determined (ELISA assay) and the role of Fk in MAC cytokine gene expression was assessed by silencing the Fk receptor in both cell types. The results showed that subsequent to the interaction with SMC, MAC exhibit: (1) a general increased expression of chemokines (the highest fold increase: VCC-1 and GRO-α) and of some interleukins, such as interleukins IL-5 (∼8-fold) and IL-6; (2) an increased Fk expression that in turn induces expression of: CXCL17, CCL19, CCL2, CXCL10, CXCL12, CXCL4, CXCL7, CCL4, CCL18, CXCL16, CXCL1 and IL-27; (3) in the presence of Rs, a predominant increased expression of interleukins (the highest fold increase: IL-6, IL-27, IL-23 and IL-5) and an augmented expression of some chemokines such as MIP-1β, GRO-α and CCL1. In addition, the secretome collected from the SMC-MAC co-culture increased human monocytes chemotaxis. DAVID analysis of the data revealed that the switch of MAC to a pro-inflammatory phenotype, prime the cells to intervene in the immune response, chemotaxis and inflammatory response. In conclusion, MAC cytokines expression is considerable augmented upon their interaction with SMC and Fk and Rs have distinct immunomodulatory roles: Fk predominantly increases the pro-angiogenic and inflammatory chemokines expression and Rs mostly the pro-inflammatory interleukins with consequences on monocyte chemotaxis. The novel data could help to develop targeted nanotherapies to reduce leukocyte chemotaxis and the ensuing inflammatory process associated with atherosclerosis.